اغتراب اللغة وأدبية الكتابة الشذرية في الخطاب الصوفي (كتاب النطق والصمت لمحمد بن عبد الجبار النفري أنموذجا) - النية, بوبكر (جامعة الوادي - University of Eloued, 2019)
الملخص: للكتابة الصوفية خصوصيات عدّة، يمكن فهم ذلك من خلال التشكيل اللغوي الذي يشيّده الصوفي، أو من خلال المضامين التي يوظّفها، وإن كانت طبيعة الأشكال تختلف عن طبيعة المضامين فإن كليهما غالبا ما يكون شيئا واحدا في الكتابة الصوفية، حيث الشكل هو المعنى في حد ذاته، يظهر ذلك حينما يعمل الصوفي على تحرير دوال اللغة عن مدلولاتها تحريرا مطلقا حتى يبدو أنها لا تعني شيئا، لكنها تحمل في عمقها كل المعنى حسب ما يعتقده الصوفي الذي يبدو متيقنا أنّ معنى اللغة في مبناها، لذلك غالبا ما يظهر على سطح الكتابة الصوفية سمات التشظي والتفكك والتشذر، لكن في جوهرها تعني الالتحام والاتصال والتماهي. مثلما هو الحال في "الكتابة الشذرية" التي نجد لها حضورا في تراثنا الصوفي، خاصة عند "النفّري" في كتابه "النطق والصمت" مثلما سنوضح في هذه البحث Abstract : Mystical writing several peculiarities that can be understood through the Mystic to be built by linguistic composition, or by content excellence, although the nature of different forms of content both often have one thing in writing a Sufi, form is meaning in itself, shows that when working Mystic edit language functions for absolute liberalization means until they seem to mean nothing, but in depth all the meaning by what other mystic who seems convinced that the meaning of the language in its building, because it often appears on the writing surface of Sufism fragmentation and disintegration and characteristics waltshzer, but in essence means admission to the Or communication and identification. This method writing the alshzerih" find her presence at the Mystic heritage, especially when "elnefary" in his book "speech and silence", as we will show in this study. Keywords: language, Mystical, write alshzerih, elnefary, speech and silence.
مقال
Keywords: اللغة، الصوفية، الكتابة الشذرية، النفّري، النطق والصمت; Keywords: language, Mystical, write alshzerih, elnefary, speech and silence.